High central venous pressure amplitude predicts successful defibrillation in a porcine model of cardiac arrest. (April 2023) - Balzer, Claudius; Eagle, Susan S.; Yannopoulos, Demetris; Aufderheide, Tom P.; Riess, Matthias L.
Abstract: Aim: Increasing venous return during cardiopulmonary resuscitation (CPR) has been shown to improve hemodynamics during CPR and outcomes following cardiac arrest (CA). We hypothesized that a high central venous pressure amplitude (CVP-A), the difference between the maximum and minimum central venous pressure during chest compressions, could serve as a robust predictor of return of spontaneous circulation (ROSC) in addition to traditional measurements of coronary perfusion pressure (CPP) and end-tidal CO2 (etCO2 ) in a porcine model of CA. Methods: After 10 min of ventricular fibrillation, 9 anesthetized and intubated female pigs received mechanical chest compressions with active compression/decompression (ACD) and an impedance threshold device (ITD). CPP, CVP-A and etCO2 were measured continuously. All groups received biphasic defibrillation (200 J) at minute 4 of CPR and were classified into two groups (ROSC, NO ROSC). Mean values were analyzed over 3 min before defibrillation by repeated-measures Analysis of Variance and receiver operating characteristic (ROC). Results: Five animals out of 9 experienced ROSC. CVP-A showed a statistically significant difference (p = 0.003) between the two groups during 3 min of CPR before defibrillation compared to CPP (p = 0.056) and etCO2 (p = 0.064). Areas-under-the-curve in ROC analysis for CVP-A, CPP and etCO2 were 0.94 (95% Confidence Interval 0.86, 1.00), 0.74 (0.54, 0.95) and 0.78 (0.50, 1.00), respectively. Conclusion: In our study, CVP-A was a potentially useful predictor of successful defibrillation and return of spontaneous circulation. Overall, CVP-A could serve as a marker for prediction of ROSC with increased venous return and thereby monitoring the beneficial effects of ACD and ITD.